Risk Factors Predicting the Survival of Pediatric Patients with Relapsed/Refractory Non-Hodgkin Lymphoma Who Underwent Hematopoietic Stem Cell Transplantation: A Retrospective Study from the Turkish Pediatric Bone Marrow Transplantation Registry - Hazar, Volkan; Kesik, Vural; Karasuc, Gulsun Tezcan; Ozturk, Gulyuz; Kupesiz, Alphan; Kilic, Suar Caki; Yesilipek, Akif c (Taylor & Francis Ltd, 2018)
We examined outcomes of 62 pediatric patients with relapsed or refractory non-Hodgkin lymphoma (rr-NHL) who underwent hematopoietic stem cell transplantation (HSCT). The overall survival (OS) and event-free survival (EFS) rates were 65% and 48%, respectively. Survival rates for patients with chemosensitive disease at the time of HSCT were significantly higher than those of patients with chemosensitive disease (69% vs. 37%, p = .019 for OS; 54% vs. 12%, p <. 001 for EFS; respectively). A chemoresistant disease at transplantation was the only factor that predicted a limited OS (hazard ratio = 10.00) and EFS (hazard ratio = 16.39) rates. Intensive chemotherapy followed by HSCT could be an effective strategy for treating children with rr-NHL and may offer improved survival for a significant group of pediatric patients, particularly those with chemosensitive disease at transplantation.
Keywords: Relapsed or Refractory Non-Hodgkin Lymphoma; Children and Adolescents; Hematopoietic Stem Cell Transplantation